Perencanaan Instalasi Pengolahan Air Limbah Domestik Perumahan Bumi Mas BTN Magaga Kota Kendari - Aspin, Aspin; Bafadal, Ishak; Rosdiana, Rosdiana (Universitas Muhammadiyah Kendari, 2021)
Currently, the Bumi Mas BTN Magaga housing only has a septic tank in each house and a drainage channel for housing liquid waste. Waste, which mainly comes from kitchen and bathroom activities, is directly discharged into the drainage and forwarded to the nearest river without any wastewater treatment. If this continues, it will pollute the nearby river water. So that, the purpose of this research is how to design domestic wastewater treatment for Bumi Mas Housing BTN Magaga. The type of research used in this study is using quantitative research, with data collection methods namely observation, interviews, and literature study. Waste water treatment plant (WWTP) planning for Bumi Mas Housing BTN Magaga with a land requirement of 56.15 m2 wide (21.2 m long × 10.2 m wide) and a waste discharge of 2.8 m³/hour using an up flow biofilter system consisting of a collection tank with dimensions of 2.4 × 1.2 × 1 m tub volume 2.8 m3 and residence time of 1 hour, fat separator tank with dimensions of 2.4 m × 1.2 m × 1 m tub volume 8.4 m3 residence time 1 hour, equalization tank 3.4 m × 1.7 m × 1 m and a tank volume of 5.6 m3 with a residence time of 2 hours, a septic tank 6 m × 3 m × 4 m and a tub volume of 66 m3 with a residence time of 6 hours, a biofilter 6 m × 3 m × 2 m and a tub volume of 33.6 m3 with a residence time of 12 hours, and a final settling tank with dimensions of 4.20 m × 2.10 m × 1 m with a volume of 8.4 m3 with a residence time of 4 hours.